2014
DOI: 10.1016/j.neuron.2014.05.013
|View full text |Cite
|
Sign up to set email alerts
|

CORTECON: A Temporal Transcriptome Analysis of In Vitro Human Cerebral Cortex Development from Human Embryonic Stem Cells

Abstract: Many neurological and psychiatric disorders affect the cerebral cortex, and a clearer understanding of the molecular processes underlying human corticogenesis will provide greater insight into such pathologies. To date, knowledge of gene expression changes accompanying corticogenesis is largely based on murine data. Here we present a searchable, comprehensive, temporal gene expression data set encompassing cerebral cortical development from human embryonic stem cells (hESCs). Using a modified differentiation p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
188
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 181 publications
(208 citation statements)
references
References 63 publications
(78 reference statements)
20
188
0
Order By: Relevance
“…Piezo1 also is identified in public gene-expression databases from human embryonic stem (hES) cells (45), mesenchymal stem cells (46), and neural stem cells (47,48). Of particular interest, van de Leemput et al (48) differentiated hES cells into brain organoids to study changes in gene expression accompanying human corticogenesis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Piezo1 also is identified in public gene-expression databases from human embryonic stem (hES) cells (45), mesenchymal stem cells (46), and neural stem cells (47,48). Of particular interest, van de Leemput et al (48) differentiated hES cells into brain organoids to study changes in gene expression accompanying human corticogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, van de Leemput et al (48) differentiated hES cells into brain organoids to study changes in gene expression accompanying human corticogenesis. Their RNA-seq database (cortecon.…”
Section: Discussionmentioning
confidence: 99%
“…The CORTECON system is generated by analyzing RNA-Seq data with nine samples from day 0 to day 77 of the differentiating hESCs (20). PCC assays revealed that the CORTECON system could not reveal the conversion from the pluripotent epiblast to the neural lineage, which progresses quickly during the early development of the human nervous system (Fig.…”
Section: Comparative Analysis Validates Module 3 Associated Day 8/10 mentioning
confidence: 99%
“…Given that intrinsic regulators, especially TFs, play essential roles in the neural commitment (20,33,34), we sought to identify key TF genes in each of the five modules. By overlapping the stagespecific genes with TF database (35) (www.transcriptionfactor.…”
Section: Regulation Network Of Transcription Factor Genes During Hescmentioning
confidence: 99%
See 1 more Smart Citation